Humanistična branja Sofoklove Antigone in humanistično razumevanje humanega - Senegačnik, Brane (Primerjalna književnost, 2018)
(Early) Humanist reception of Greek tragedy is characterized by Aristotelian interpretation of tragedy according to contemporary understanding of Poetics (Lurie, Mola). In this frame Sophocles' Antigone was more or less flattened into a moral object lesson about the punishment of a tyrant abusing his power. Humanist commentators and translators showed very little interest in the play's literary and philosophical complexity that made it one of the most admired and influential texts of the Western culture over the past three centuries. However, we should not overlook the excessive tendency towards intellectualization of tragedy, characteristic of many major modern readings (M. Heath), on the one hand, and the expectations of the original audience, on the other: in both its literary and political context tragedy was supposed to teach (N. Croally). Admitting that there is a moral to Antigone does not involve using simple moralistic terms like those used by e. g. Camerarius; one would rather see it as a hint at indispensability of individual human being both for the correct understanding of human nature and for ethical being in the world.
Keywords: Antigona (drama); humanizem; humanost; književnost in etika; literarne interpretacije; Sophocles; starogrška književnost; tragedija